On Large Deviations of Stochastic Integrodifferential Equations with Brownian Motion - Haseena, A.; Suvinthra, M.; Annapoorani, N. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, a Freidlin-Wentzell type large deviation principle is established for the stochastic integrodifferential equation driven by finite dimensional Brownian motion. Both the additive and multiplicative noise cases are considered here. Large deviation principle for additive noise case is established via contraction principle whilst weak convergence approach is employed to obtain the same for the multiplicative noise case.